Analisis Yuridis terhadap Putusan Pengadilan Tinggi Tata Usaha Negara Surabaya terkait Penundaan Pemilihan Kepala Desa yang Tidak Dilaksanakan oleh Bupati Timor Tengah Selatan: Putusan Nomor 141/B/2022/PT.TUN.SBY - Apolonius Dacunha Dagung; A. Resopijani; Rizal S. Thene (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This research is motivated by the failure of the Regent of South Central Timor to implement the decision of the Surabaya Administrative High Court regarding the postponement of the Bileon Village Head election, despite the decision having permanent legal force. This action contradicts the rule of law principle stipulated in Article 1 paragraph (3) of the 1945 Constitution, which requires all government actions to be based on law. The study aims to analyze the legal considerations of the Regent in issuing Decree Number 13/KEP/HK/2022 on the election postponement, examine the legal reasoning of the Administrative High Court judges, and assess the effectiveness of enforcing administrative court decisions in ensuring legal certainty and administrative justice. The research employs a normative juridical approach using statutory and case approaches, with descriptive qualitative analysis based on primary, secondary, and tertiary legal materials. The findings indicate that the Regent’s decree lacks a valid legal basis and violates Law Number 30 of 2014 on Government Administration and Law Number 6 of 2014 on Villages, breaching principles of good governance, particularly legal certainty, proportionality, and justice. The court determined that the Regent’s action constituted abuse of authority. The failure to implement the decision highlights weaknesses in administrative court enforcement mechanisms, emphasizing the need for stricter regulations and sanctions for public officials who disregard court rulings to ensure compliance and uphold legal certainty.